PENGEMBANGAN MEDIA AUDIO VISUAL KINEMASTER DALAM PEMBELAJARAN TEMA 8 PADA KELAS IV DI SD NEGERI SERANG 20 - Pirdayuni; Damanhuri; Aan Subhan Pamungkas (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the development process, the feasibility of the developed Kinemaster audio-visual media, and the student’s responses to the Kinemaster audio-visual media in thematic learning. The study explained in this article was conducted at SD Negeri Serang 20. This study involved 23 students of class IV in a limited trial. The method used in the study refers to the steps of development research developed by Borg and Gall in Sugiyono by doing (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trial. The instrument used was a questionnaire sheet for media validation with a percentage of 72.75% material experts with a percentage of 89.2% and a student response questionnaire sheet of 89.5%. Based on the validation analysis, it could be concluded that the quality of the Kinemaster Audio-Visuall Media developed in the study was in the very feasible category, while the results of student responses to the Kinemaster AudioVisual Media were in the very good category.